Isolasi, Karakterisasi, dan Uji Aktivitas Antibakteri dari Bakteri Endofit Daun Kelor (Moringa oleifera) - Sadikin, Nadya Audina Nurkhafiya; Bintari, Siti Harnina; Widiatningrum, Talitha; Dewi, Pramesti (Universitas Negeri Semarang, 2021)
Endophytic bacteria are beneficial microorganisms that interact with host plants without causing any interference or damage to plants. Moringa oleifera is a medicinal plant that contains secondary metabolites and has antibacterial properties. The aim of this research is to isolate and characterize endophytic bacteria from Moringa oleifera leaves, and to test the antibacterial activity against pathogenic bacteria (Escherichia coli and Bacillus subtilus). The results of the isolation of Moringa leaf endophytic bacteria (Moringa oleifera) obtained amounted to one isolate. Based on the results of the catalase test, gram staining and spore observation, moringa oleifera leaf endophytic bacteria included in the genus Bacillus. The antibacterial test begins with the production of secondary metabolites of Moringa oleifera leaf endophytic bacteria, measures the rate of bacterial growth and tests the antibacterial activity using the Kirby Bauer method with paper disks. Observational data were analyzed statistically using ANOVA and further tests with Duncan (sig <0.05). Antibacterial activity test results showed that the incubation time of endophytic bacteria affected the growth of Escherichia coli and Bacillus subtilus bacteria. The incubation time of 10 hours showed the highest inhibition zone diameter of Escherichia coli and Bacillus subtilus bacteria respectively of 7.5 mm and 1.8 mm. The formation of inhibitory zones indicates the presence of secondary metabolite compounds from Moringa leaf endophytic bacteria which have an antibacterial effect. Bakteri endofit merupakan mikroorganisme menguntungkan yang berinteraksi dengan tanaman inang tanpa menyebabkan gangguan atau kerusakan pada tanaman. Kelor (Moringa oleifera) merupakan tanaman obat yang mengandung metabolit sekunder dan berkhasiat sebagai antibakteri. Tujuan penelitian ini adalah mengisolasi dan mengkarakterisasi bakteri endofit dari daun kelor, serta menguji aktivitas antibakteri terhadap bakteri patogen (Escherichia coli dan Bacillus subtilus). Hasil isolasi bakteri endofit daun kelor (Moringa oleifera) yang diperoleh berjumlah satu isolat. Berdasarkan hasil uji katalase, pewarnaan gram dan pengamatan spora, bakteri endofit daun kelor termasuk ke dalam genus Bacillus. Uji antibakteri dimulai dengan produksi metabolit sekunder bakteri endofit daun kelor, pengukuran laju pertumbuhan bakteri dan uji aktivitas antibakteri menggunakan metode Kirby bauer dengan paper disk. Data hasil pengamatan dianalisis statistik menggunakan ANOVA dan uji lanjut dengan Duncan (sig < 0.05). Hasil uji aktivitas antibakteri menunjukkan bahwa waktu inkubasi bakteri endofit berpengaruh terhadap pertumbuhan bakteri Escherichia coli dan Bacillus subtilus. Waktu inkubasi selama 10 jam menunjukan diameter zona hambat tertinggi terhadap bakteri Escherichia coli dan Bacillus subtilus berturut-turut sebesar 7.5 mm dan 1.8 mm. Terbentuknya zona hambat mengindikasikan adanya senyawa metabolit sekunder dari bakteri endofit daun kelor yang memiliki efek antibakteri.